ANALISIS LAPORAN ARUS KAS SEBAGAI ALAT PENGAMBILAN KEPUTUSAN MANAJEMEN PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Mohaa=mmad Adib Azmi; isroil isroil; Hasun Hasun; Diana Lestari (JURNAL AKUNTANSI DAN INVESTASI, 2022)
This study aims to determine the financial performance of a company by using an analysis of cash flow statements for companies listed on the Indonesia Stock Exchange for the 2016-2020 period. This research uses qualitative and quantitative descriptive research types that aim to describe the conditions that occur in order to see, reveal, and accurately describe the things that are being faced and draw conclusions. The data analysis technique used is the ratio analysis of cash flow statements. The results of the research from calculating cash flow reports and analyzing cash flow statements show that the effectiveness of PT Berlina Tbk's cash flow performance over a period of 5 years (2016-2020) is less effective. Judging from the calculation of cash flow statements, there are more ratios below number 1 which illustrates that the company unable to fulfill its obligations and commitments. This is because during 2014-2016 PT Berlina Tbk has not presented a cash flow report and conducted an analysis of cash flow reports so that the cash flow performance cannot be known earlier for improvement efforts to be made, especially in increasing the company's cash flow.